A methodology for simulating plasticity induced crack closure and crack shape evolution based on elastic–plastic fracture parameters. (January 2021) - Escalero, Mikel; Muniz-Calvente, Miguel; Zabala, Haritz; Urresti, Iker; Branco, Ricardo; Antunes, F.V.
Abstract: A methodology for simulating plasticity induced crack closure and crack shape evolution based on elastic–plastic fracture parameters is proposed, which represents a new way to predict fatigue crack growth in small and large scale yielding scenarios. The methodology consists in solving iteratively a single elastic–plastic finite element model, for which the load history is kept by remeshing and mapping and crack advance is performed by node releasing. Aiming to illustrate and validate the approach, the growth of an initially straight crack is simulated in a compact tension specimen subjected to small scale yielding conditions, using the plastic crack tip opening displacement range ( Δ CTOD p ) as the crack driving force. The predicted crack shape shows high agreement with experimental observations and the crack opening load trends are consistent with the literature, demonstrating that the methodology proposed can be relevant for further crack growth studies. Highlights: Crack closure and shape evolution are simulated considering their interaction. Load history is kept by remeshing and mapping a single finite element model. The plastic crack tip opening displacement range is used as the crack driving force. The predicted crack shape agrees well with experimental observations.